Evaluation of blue and red corn landraces - Bódi, Zoltán; Pepó, Pál; Kovács, Andrea (Acta Agraria Debreceniensis, 2007)
Corn breeding can be successful only on a broad base of genetic material. The expansion of breeding aims includes the research of germplasm materials. In our experiments, we examined 11 blue, purple and red exotic corn varieties on two locations in Hungary. We conducted a complex study to obtain more information. We studied several morphological and phenological features and determined the most important qualitative parameters (protein, fat, ash). We applied the Tassel Area Index (TAI) under Hungarian conditions and compared it with the pollen producing ability of different genotypes. Results show that there are great opportunities in exotic corn varieties. Their quality exceeds that of the yellow ones in many cases. There are significant differences in yield and nutritional parameters. The favorable nutritional composition is not coupled with great productivity. Based on their flowering time and their agronomical features, they can be cultivated under Hungarian conditions as well. They match the new breeding aims, so they can be used as functional food or energy plants. With their high pollen producing ability and TAI, they can be utilized as markers in future pollen research.